2007
DOI: 10.1371/journal.pmed.0040167
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Conditions Influence Adult Progesterone Levels

Abstract: BackgroundAverage profiles of salivary progesterone in women vary significantly at the inter- and intrapopulation level as a function of age and acute energetic conditions related to energy intake, energy expenditure, or a combination of both. In addition to acute stressors, baseline progesterone levels differ among populations. The causes of such chronic differences are not well understood, but it has been hypothesised that they may result from varying tempos of growth and maturation and, by implication, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 57 publications
4
79
1
Order By: Relevance
“…In an earlier paper, we found that infectious disease load was a significant predictor of age at menopause among a larger sample of Bangladeshi women, but this variable was not significant in the analyses here of a smaller group of women sampled for hormone levels (60). We have similarly suggested, however, in past papers that life history trade-offs could explain differences in other reproductive and developmental parameters between Bangladeshis who grow up in contrasting UK and Bangladeshi environments, including ages at adrenarche and menarche, levels of salivary progesterone and rates of ovulation (41)(42)(43)84).…”
Section: Hormone Levelsmentioning
confidence: 69%
See 1 more Smart Citation
“…In an earlier paper, we found that infectious disease load was a significant predictor of age at menopause among a larger sample of Bangladeshi women, but this variable was not significant in the analyses here of a smaller group of women sampled for hormone levels (60). We have similarly suggested, however, in past papers that life history trade-offs could explain differences in other reproductive and developmental parameters between Bangladeshis who grow up in contrasting UK and Bangladeshi environments, including ages at adrenarche and menarche, levels of salivary progesterone and rates of ovulation (41)(42)(43)84).…”
Section: Hormone Levelsmentioning
confidence: 69%
“…More recently, effects of the developmental environment on adult ovarian function have also been assessed (41)(42)(43). In our earlier work, for example, we found significant differences in levels of reproductive steroids, length of the reproductive lifespan, and rates of ovulation among age-and socioeconomically matched Bangladeshi women depending on whether they had grown up in Bangladesh or the UK (32,(41)(42)(43).…”
Section: Introductionmentioning
confidence: 83%
“…Several lifestyle and reproductive factors are known to influence levels of ovarian steroid hormones and fertility in healthy women [27,[34][35][36][37][38][39]. Therefore, we analysed differences between genotypes with at least one ApoE4 allele and without ApoE4 alleles in age, reproductive characteristics (menarcheal age, number of children, age at first reproduction, length of menstrual cycle), body size (at birth and in adulthood), levels of daily physical activity and of education.…”
Section: (D) Statistical Analysismentioning
confidence: 99%
“…However, this negates neither the importance of the potential mechanism, nor its implications for the rest of the world and the changing disease patterns it is experiencing. Economic development over generations may increase levels of sex steroids [6]. One key exposure (pubertal sex steroids) could provide a simple sociobiological explanation for the secular trends in diabetes and ischaemic heart disease that occur with economic development.…”
mentioning
confidence: 99%